Potret Kehidupan Maulana: Sosok Siswa Kaya, Mandiri, dan Berprestasi: Portrait of Maulana's Life: A Wealthy, Independent, and Outstanding Student - Nafa Izah; Nanang Martono; Mintarti Mintarti (Society, 2020)
This study aims to describe a wealthy student’s habitus who does not get enough attention from parents but can make school achievements. Parents’ role is vital in children’s learning development process and becomes an encouragement to increase children’s enthusiasm for learning. In this case, wealthy students with achievements are often seen as something normal. However, upper-class students who do not get enough attention from their parents because of being busy at work but can make achievements are exciting things to study, especially to observe the habitus that shapes them. This study uses a qualitative method with a life history approach. This study’s single informant is Maulana, a high school student in Cilacap city, Central Java Province, Indonesia. Selection of informant using a purposive sampling technique. The study results indicate that a separate living house forms the habitus of Maulana as an independent student. Independent, in this case, means that he has the initiative to learn without coercion. The achievements he made were a form of strategy to attract the attention of his parents. The achievements that are always compared to his older siblings have boosted Maulana’s enthusiasm to improve his achievements. In this case, the study results stated that the habitus is formed from the capital (social, economic, cultural, and symbolic) of the individual. Parents’ busyness is not a problem in getting their performance at school.